Impacts of flooding on the lives of the elderly people and their coping strategies in Tokwe Mukosi - Mandipaza, Moreblessing S. (Midlands State University, 2017)
The research was concerned on investigating on the impacts of flooding on the lives of the elderly people who have been affected by the Tokwe Mukosi floods and their coping strategies in Masvingo Province. Quite a number of researches had focused on the impacts of floods on people, but little research has been seen focusing on the older adults. The research used a phenomenological research design to find out on the impacts of the flooding on the elderly adults and their coping strategies. Snowball sampling was used to select the number of participants and face to face interviews were done. The results of the study revealed psychological impacts such as anger and frustration, self- esteem and stress affecting the elderly subjects. Social impacts found include loss of crops and livestock, property damage, poor sanitation and health facilities and total change of life. The coping strategies found were slaughtering and selling livestock, going to church and seeking help from other organisations. The researcher concluded that flooding has quite a number of negative impacts on people’s lives, particularly, the elderly ones. These impacts are seen as the elderly are left helpless as they lose almost all their life achievements which range from property, livestock and crops. However, the research found out that although they tried to cope with the flooding, the coping strategies were short lived as they could not last for long. The researcher recommended that disaster preparedness is always advisable and should also cover rural areas. Other recommendations include that counselling should be provided to the elderly victims for them to be able to cope with disasters like floods and that the elderly people should be grouped on their own and be separated from other age groups in case of a disasters as they need more attention due to their age than other age groups who are still able bodied.